Nurse plants and seed provenance in the restoration of dry Chaco forests of central Argentina - Venier, P.; Ferreras, A.E.; Lopez Lauenstein, Diego; Funes, G. (Elsevier, 2022)
In degraded dry environments, a promising restoration strategy involves nurse plants and their microsites, which facilitate species recruitment. Different nurse plant species might provide different microclimatic and soil conditions under their canopy as well as diverse herbivory protection strategies. Seed provenance of target species is also relevant to restoration success. We evaluated the effectiveness of two native woody species (Parkinsonia praecox and Larrea divaricata) as nurse plants for Prosopis flexuosa establishment to be used in restoration programs in semiarid Chaco forests of central Argentina. We conducted a field experiment in a degraded site to analyze microclimatic and soil characteristics under the canopy of the nurse species and in bare soil. In these microsites we planted 240 P. flexuosa saplings to evaluate their performance during two years, including local and non-local provenances. Both nurse species were safer sites for recruitment than bare soil, because under their canopies microclimatic characteristics were ameliorated and soil nutrient availability was increased, with the best sapling performance being under P. praecox crown. Of the total plants that survived (42%), most of them did so under the nurses (74%). Height of P. flexuosa saplings decreased regarding initial height, in the three microsites. Herbivory greatly limited sapling establishment success in bare soil; therefore, both nurses would have an important role in providing shelter. P. flexuosa performance was not influenced by provenance. Including P. praecox and L. divaricata as nurse plants in restoration strategies would promote the use of established vegetation in recovering the semi-arid Chaco forest.